2012
DOI: 10.4018/ijepr.2012070102
|View full text |Cite
|
Sign up to set email alerts
|

Exploring E-Planning Practices in Different Contexts

Abstract: As planners and decision-makers experiment with information and communication technologies (ICTs), it’s important to explore and analyze these attempts in different planning systems and contexts. The aim of the article is to compare the use of and aspirations attached to e-planning in Helsinki, Finland and Sydney, Australia. This comparison will highlight the interrelationship between planning context and its amenability to an e-planning approach and shows there are shared themes in both cases: firstly, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…Rantanen and Faehnle (2017, p. 1) argue ICTs are supporting increased social self-organisation, which in turn is driving a 'new phase of urbanisation' in which planning processes and outcomes are increasingly 'user-driven' and decentralised. Wallin, Horelli, and Saad-Sulonen (2010) argue that ICTs are now facilitating co-learning, and broadening the reach of planners' engagement activities, and enable those who 'do not live in the place but feel connected to it, or other active groups who wish to be involved in the planning' (Horelli, 2013, p. 142). A review of three Finnish case studies by Saad-Sulonen (2014) also found that planners and communities are increasingly interacting beyond traditional communicative Web 2.0 ICTs such as emails, and online consultation forms, and the gap between citizens and planners is narrowing thanks to new Web 3.0 based ICTs.…”
Section: Planning 30: a Technological Turn In Planning Paradigms?mentioning
confidence: 99%
“…Rantanen and Faehnle (2017, p. 1) argue ICTs are supporting increased social self-organisation, which in turn is driving a 'new phase of urbanisation' in which planning processes and outcomes are increasingly 'user-driven' and decentralised. Wallin, Horelli, and Saad-Sulonen (2010) argue that ICTs are now facilitating co-learning, and broadening the reach of planners' engagement activities, and enable those who 'do not live in the place but feel connected to it, or other active groups who wish to be involved in the planning' (Horelli, 2013, p. 142). A review of three Finnish case studies by Saad-Sulonen (2014) also found that planners and communities are increasingly interacting beyond traditional communicative Web 2.0 ICTs such as emails, and online consultation forms, and the gap between citizens and planners is narrowing thanks to new Web 3.0 based ICTs.…”
Section: Planning 30: a Technological Turn In Planning Paradigms?mentioning
confidence: 99%
“…Recommendation 2: There is a need for new ontological lenses that embrace not only expertise but also local knowledge that produces both numerical and experiential data. Instead of defining specific technological applications, which might soon become late, the legislation should embrace an ecosystem of tools, digital and non-digital [23]. These should be embedded in an approach that expands the focus to and anticipates [42] the emergence of new openings in urban and eco-social development.…”
Section: Conclusion 2: the Need For New Methodological Openings In Ur...mentioning
confidence: 99%
“…As flat ontology implies an application of a relational and dynamic epistemology, EP has adopted an eco-system of digital and non-digital tools for empowerment and analysis [23]. The methodology comprises a variety of enabling methods, as well as future-oriented research tools, including community informatics and city information modelling [9,23,24].…”
Section: Flat Ontology and Expanded Urban Planning As A Theoretical F...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we drew on insights gained from previous map table-based PSS workshops [18,21]. Those user stories and experiences combined with the required baseline functionality of an online annotated map [40,41] formed the starting point for the conceptualization of the tool that is presented in this article. Figure 3 shows the workflow of our study that is elaborated in the following subsections.…”
Section: Methodsmentioning
confidence: 99%